2012
DOI: 10.5402/2012/489605
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Low-Grade Low-Heat-Rejection Diesel Engine with Crude Pongamia oil

Abstract: Investigations are carried out to evaluate the performance of a low heat rejection (LHR) diesel engine with ceramic coated cylinder head [ceramic coating of thickness 500 microns is done on inside portion of cylinder head] with different operating conditions [normal temperature and pre-heated temperature] of crude Pongamia oil (CPO) with varied injection pressure and injection timing. Performance parameters and pollution levels are determined at various magnitudes of brake mean effective pressure. Combustion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…editor@iaeme.com Experiments were conducted on medium grade LHR engine which consisted of air gap insulated piston with superni crown and air gap insulated liner with superni insert with advanced injection timings and increased injection pressure with vegetable oils. [26][27][28]. They reported that particulate matter decreased by 20% and NOx levels increased by 45% at peak load operation with LHR engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…editor@iaeme.com Experiments were conducted on medium grade LHR engine which consisted of air gap insulated piston with superni crown and air gap insulated liner with superni insert with advanced injection timings and increased injection pressure with vegetable oils. [26][27][28]. They reported that particulate matter decreased by 20% and NOx levels increased by 45% at peak load operation with LHR engine.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were carried out with high grade LHR engine, which consisted of air gap insulated piston, air gap insulated liner and ceramic coated cylinder head with vegetable oils [29][30][31]. They reported that LHR engine further increased NOx levels and decreased smoke levels.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were extended to crude vegetable oil operation on high grade LHR engine. [24][25][26]. The optimum injection timing was observed to be 29 o bTDC with high grade LHR combustion chamber with crude vegetable oil operation.…”
Section: Introductionmentioning
confidence: 99%
“…The heat resistant coating reduces the heat transfer to the coolant system and improves the thermal efficiency by increasing the energy availability in the exhaust [1][2][3][4][5][6][7]. The diesel engine with its combustion chamber walls are insulated by heat flow resistant coating is referred to as LHR engine.…”
Section: Introductionmentioning
confidence: 99%